1986
DOI: 10.1007/bf02582061
|View full text |Cite
|
Sign up to set email alerts
|

Reduced intraindividual variability of repeated cardiovascular reflex tests: An additional marker of autonomic neuropathy in insulin-dependent (type I) diabetes mellitus?

Abstract: The particular questions asked in our study were: 1. does the individual reproducibility of the cardiovascular reflex tests differ between healthy controls and patients suffering from type I diabetes mellitus and 2. if there is a difference, do the different cardiovascular reflexes vary in this regard? Nine healthy controls (4 women, 5 men, age 31 +/- 2.1 years) and 11 type I diabetics (4 women, 7 men, age 30.9 +/- 5.6 years, duration of diabetes 3.23 years) underwent the following tests 6 times in a 12-h peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…However, recently the value of this method during exercise has been questioned, because the indirect method underestimates especially the intra-arterial diastolic pressure (Kaijser, 1987). Additionally, in the present study, in accordance with previous studies (Comi et al, 1986;Kronert et al, 1986), the repeatability of blood pressure responses was very poor. 0.10, lower 80% tolerance limit (lowest normal value); 0-025, lower 95% tolerance limit (lowest borderline).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, recently the value of this method during exercise has been questioned, because the indirect method underestimates especially the intra-arterial diastolic pressure (Kaijser, 1987). Additionally, in the present study, in accordance with previous studies (Comi et al, 1986;Kronert et al, 1986), the repeatability of blood pressure responses was very poor. 0.10, lower 80% tolerance limit (lowest normal value); 0-025, lower 95% tolerance limit (lowest borderline).…”
Section: Discussionsupporting
confidence: 91%
“…The coefficients of variation of max/min and IIHR were 10 and 14%, thus showing satisfactory repeatability. Previous studies have concluded that the repeatability of madmin is good (Ewing et al, 1978;O'Brien et al, 1986a;Comi et al, 1986;Kronert et al, 1986).…”
Section: (Upper 80% Tolerance Limit) and The Highest Upper Borderline Ismentioning
confidence: 99%
“…Adding to this complexity, there is evidence that the reproducibility of the cardiovascular reflex tests are higher in diabetes patients than in healthy controls due to a well-described reduction in HRV in the diabetes population. [26][27][28] Further studies in the diabetes population are therefore necessary to investigate whether or not it is of clinical relevance to perform self-monitoring of CAN.…”
Section: Discussionmentioning
confidence: 99%